Addition of anal encirclement to perineal proctosigmoidectomy: a retrospective review - Amery, Aiya; Marritt, Kayla; Baig, Zarrukh; Roy, Haven; Gill, Dilip; Ginther, Nathan (Frontiers in Surgery, 2025)
BackgroundThe optimal approach for the surgical management of rectal prolapse is individualized based on anatomical, functional, and surgical factors. In patients with significant comorbidities, perineal approaches are often preferred even though they are associated with higher recurrence rates compared to an abdominal approach. Although anal encirclement was one of the first procedures described for this condition, it is seldom employed given its high recurrence rates. There is currently a lack of data addressing a combination surgery, wherein both a perineal proctosigmoidectomy and anal encirclement are performed simultaneously.AimsTo evaluate the efficacy of combining perineal proctosigmoidectomy with anal encirclement using Nylon sutures compared to perineal proctosigmoidectomy alone.MethodsThis was a single institution, non-randomized, retrospective study conducted at the Royal University Hospital, Saskatoon, Saskatchewan, Canada (July 2017 to October 2022). Patients over the age of 18 with full-thickness rectal prolapse who underwent either perineal proctosigmoidectomy alone or perineal proctosigmoidectomy with anal encirclement were included. There were 23 patients in the perineal proctosigmoidectomy group and 21 patients in the perineal proctosigmoidectomy with anal encirclement group. The primary outcome was prolapse recurrence. Secondary outcomes included operative time, length of hospital stay, and post-operative complications.ResultsPatients who received perineal proctosigmoidectomy with anal encirclement had significantly lower rates of recurrent prolapse (9.5%) compared to perineal proctosigmoidectomy alone (34.8%) (p = 0.02). Patients who underwent the combined procedure had a shorter length of stay by 2.3 days (p = 0.03). There was no difference in post-operative complications or operating time.ConclusionsRoutine anal encirclement in perineal proctosigmoidectomy reduces recurrence rates and length of stay without increasing operating time or complications.